1987
DOI: 10.1128/jb.169.9.4349-4354.1987
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the ADPglucose pyrophosphorylase (glgC) and glycogen synthase (glgA) structural genes from Salmonella typhimurium LT2

Abstract: The structural genes of ADPglucose pyrophosphorylase (glgC) and glycogen synthase (glgA) from Salmonella typhimurium LT2 were cloned on a 5.8-kilobase-pair insert in the Sail site of pBR322. A single strand specific radioactive probe containing the N terminus of the Escherichia coli K-12 glgC gene in M13mp8 was used to hybridize against a S. typhimurium genomic library in X1059. DNA from a plaque showing a positive hybridization signal was isolated, subcloned into pBR322, and transformed into E. coli K-12 RR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It was initially tempting to attribute the absence of ADPglucose pyrophosphorylase activity to the major sequence change that was found in the glgC gene of the three strains of S. Gallinarum, which had been isolated from different parts of the world, particularly since the product of the glgC gene is responsible for considerable regulation of glycogen synthesis through allosteric competition by fructose 1,6-bisphosphate (Leung & Preiss, 1987a). However, the absence of this change in S. Pullorum suggested that this was not the sole reason.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially tempting to attribute the absence of ADPglucose pyrophosphorylase activity to the major sequence change that was found in the glgC gene of the three strains of S. Gallinarum, which had been isolated from different parts of the world, particularly since the product of the glgC gene is responsible for considerable regulation of glycogen synthesis through allosteric competition by fructose 1,6-bisphosphate (Leung & Preiss, 1987a). However, the absence of this change in S. Pullorum suggested that this was not the sole reason.…”
Section: Discussionmentioning
confidence: 99%
“…4C) and CM3.1 (data not shown), although the strains are unable to accumulate glycogen within intracytoplasmic inclusions. Glycogen synthase, the product of the glgA gene, is required for the formation of the ␣-1-4-glucosidic linkage characteristic of the main polyglucose chains of glycogen, and bacteria with glgA deleted or mutated are unable to synthesize glycogen (23). Transcription of this gene was ϳ6-fold reduced…”
Section: Vol 79 2011 Coordinate Regulation Of Plasmid-responsive Gementioning
confidence: 99%
“…The bacteria, phage strains, and plasmids used in this study are as follows: E. coli K-12 JM101 [supE thi A(lac-proAB) F' traD36 proAB lacIq AM1S], E. coli K-12 JM103 [supE thi A(lac-proAB) strA endA sbcA hsdR F' traD36 proAB lacIq AM15]; bacteriophages M13 mp8, 9, 10, and 11 (17); and plasmid pPL301, which contains the S. typhimurium glgC and glgA genes on a 5.8-kilobase-pair insert on the SalII site of pBR322 (14).…”
Section: Methodsmentioning
confidence: 99%
“…The ADPglucose synthetases of E. coli and S. typhimurium are similar in that (i) they have similar subunit and native molecular weights; (ii) they have the same spectrum of activators and inhibitors; (iii) they have immunological cross-reactivity; (iv) of the first 27 amino acids in the N terminus 25 are identical; (e) genetically, the glg genes of both are clustered around 75 units on their genetic maps and are cotransducible with asd and glpD genes (28). Recently, we have cloned the glgC and glgA genes from S. typhimurium (14). This paper is a report of the nucleotide sequence, the deduced amino acid sequence, and codon usage pattern of ADPglucose synthetase from S. typhimurium.…”
mentioning
confidence: 99%